Ageing of two 5kW PV arrays at the IES-UPM after 8 years of operation - Martínez-Moreno, F. (2021)
This work analyses the degradation of two 5 kW PV arrays which are located on the roof of the Campus Sur of the Universidad Politécnica de Madrid. These systems were installed in March 2013 and they have been continuously monitored while they have been injecting power into the grid, storing at the same time its DC power and the operation conditions (effective irradiance and cell temperature). These variables allow to calculate their power at Standard Test Conditions over time and, consequently, the degradation rate for each PV array in these 8 years of operation. The linear degradations obtained are similar to the ones presented by other authors, but we have found that there is not apparent degradation in the first years of operation. Besides, it seems that shading could increase the degradation rates. These figures and phenomena can be useful for a better understanding of the actual behavior of PV systems in order to obtain more accurate energy predictions.